Dynamics and variability of the alongshore flows on the northwestern iberian margin - Teles-Machado, Ana (2014)
Tese de doutoramento, Ciências Geofísicas e da Geoinformação (Oceanografia), Universidade de Lisboa, Faculdade de Ciências, 2014